Mechanism to Sustainably Reduce Malnutrition for Urban Households in Johannesburg - Venter, Natalie (University of the Witwatersrand, Johannesburg, 2021)
Malnutrition remains as one of the most serious health problems worldwide. Evidence indicates a link between poverty and malnutrition with complex and multiple connected elements that are both causes and consequences of malnutrition. Malnutrition causes poor cognitive development and reduced physical capacity affecting human capital development, which in turn reduces productivity, slows economic growth, and perpetuates poverty. When developing strategies or mechanisms to sustainably reduce malnutrition the focus needs to be on addressing the root or basic causes as this drives the underlying and immediate causes ultimately manifesting as malnutrition. Studies recommend short- and long-term strategies to reducing malnutrition which need to be implemented simultaneously as the long-term aspects focus on increasing economic factors such as income and food security; the short-term aspects aim to provide health, education and nutrition which directly impact human capital development. Strengthening the commitment and increasing action to tackling malnutrition requires partnerships between different stakeholders namely, government, the private sector, and the development partner community. Eradicating malnutrition is vital as it lays the foundation for human capital development and is known to undermine economic growth further impacting a wide range of social factors and human rights. Investing in nutrition yields high returns of investment when implementing cost effective programs targeted towards pregnant women, infants, and young children as the phases between conception and first 1000 days of life present a window of opportunity to focus action on addressing malnutrition (The World Bank, 2006).
A Social Entrepreneurship Project Submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in Partial Fulfillment of the Requirements for the Degree of Master of Business Administration, Johannesburg 2021
Keywords: Malnutrition; Poverty and malnutrition; Developing strategies; UCTD; SDG-8: Decent work and economic growth